Variant‐level matching for diagnosis and discovery: Challenges and opportunities. Issue 6 (21st March 2022) - Rodrigues, Eliete da S.; Griffith, Sean; Martin, Renan; Antonescu, Corina; Posey, Jennifer E.; Coban‐Akdemir, Zeynep; Jhangiani, Shalini N.; Doheny, Kimberly F.; Lupski, James R.; Valle, David; Bamshad, Michael J.; Hamosh, Ada; et al.
Abstract: Here we describe MyGene2, Geno2MP, VariantMatcher, and Franklin; databases that provide variant‐level information and phenotypic features to researchers, clinicians, healthcare providers and patients. Following the footsteps of the Matchmaker Exchange project that connects exome, genome, and phenotype databases at the gene level, these databases have as one goal to facilitate connection to one another using Data Connect, a standard for discovery and search of biomedical data from the Global Alliance for Genomics and Health (GA4GH).